Diabetes Treatment with Dapagliflozin and Its Combinations: Insights from Clinical Practice - Akshay Bafna; Ajit Mehta; Rajeev Garg; Jayagopal Pathiyil Balagopalan; Rajesh Rajput; Nitin Zalte; Preethi Naik; Amarnath Sugumaran; Senthilnathan Mohanasundaram (Journal of Diabetology, 2024)
Abstract Objective: To evaluate the perception of clinicians about the association of heart failure (HF) and type 2 diabetes mellitus (T2DM) and the utilization of dapagliflozin-based combination therapies for cardiorenal protection in Indian patients with T2DM. Materials and Methods: This cross-sectional, digital questionnaire-based study involved diabetologists and consulting clinicians from pan-India and was conducted between October 2022 and March 2023. Results: Of the 982 clinicians, 871 completed the study. According to 90.93% and 47.19% of clinicians, most patients with T2DM were in the age group of 40–60 years, and cardiovascular (CV) risk is present in 3 in 10 of T2DM patients, respectively. As the initial choice of oral antidiabetic class (other than metformin), 43.86% of clinicians preferred sodium-glucose cotransporter-2 inhibitors (SGLT2i). Dapagliflozin is the most effective SGLT2i in reducing mortality/hospitalization in T2DM patients with HF (70.38%). In T2DM patients with CV/renal risk, 66.02% of clinicians recommended dapagliflozin with sitagliptin (10 mg + 100 mg strength) as SGLT2i plus dipeptidyl peptidase-4 inhibitors (DPP4i) fixed-dose combination (FDC). The use of a triple-drug FDC of dapagliflozin plus sitagliptin plus metformin was strongly recommended by 74.40% of clinicians. Early initiation and intensification with a combination of SGLT2i and DPP4i in young T2DM patients (30–50 years) inadequately managed on metformin was highly recommended (94.58%). The majority of clinicians opined that SGLT2i should be initiated in all T2DM patients with comorbidities to prevent HF complications (97.58%), and SGLT2i is underutilized in India for the treatment of HF in T2DM patients (89.21%). Conclusion: The overall observations provide insights into the usage patterns of dapagliflozin-based combination therapies for cardiorenal protection among Indian T2DM patients.